Empowering Communities: Building Healthy Life Through Unity - Sugiharto, Septiono Bangun (Department of Public Health, Faculty of Health Sciences, Jenderal Soedirman University, 2023)
Community empowerment is one strategy to help control health problems in society. Leveraging community participation to be involved in community empowerment in the health sector is not only the domain of the health sector's duties. This effort can be carried out if there is involvement of cross-sectoral roles. One of the cross-sectoral sectors that is a dynamist for community empowerment is the involvement of FKD/FKK which consists of community elements from the village area concerned. Increasing coordination between health sectors, both across programs within the Puskesmas itself, and with cross-sectors outside the Puskesmas such as sub-districts, villages/kelurahan, village midwives and FKD/FKK, as well as the business world needs to be carried out continuously and sustainably in alleviating health problems to improve degree of public health.